2018
DOI: 10.21273/horttech03893-17
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Perceptions of Landscape Plant Production Water Sources and Uses in the Landscape during Perceived and Real Drought

Abstract: Water is becoming scarcer as world population increases and will be allocated among competing uses. Some of that water will go toward sustaining human life, but some will be needed to install and support landscape plants. Thus, future water resource availability may literally change the American landscape. Recent research suggests that consumers’ attitudes and behavior toward potable water supplies have changed in other countries because of greater social awareness and increasingly widespread exposure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 24 publications
3
13
0
Order By: Relevance
“…The conjoint study produced findings consistent with prior research [8,44,66,67]. Overall, plant type was the most important product attribute, while price was the least important.…”
Section: Conjoint Findingssupporting
confidence: 80%
See 3 more Smart Citations
“…The conjoint study produced findings consistent with prior research [8,44,66,67]. Overall, plant type was the most important product attribute, while price was the least important.…”
Section: Conjoint Findingssupporting
confidence: 80%
“…In one study, participants who accurately perceived themselves to be in a drought situation had a more accurate assessment of their confidence and knowledge in conserving water in their outdoor space (i.e., they were consciously competent.) [8]. Additionally, Behe et al [9] and Knuth et al [10] found that individuals who scored high on plant expertise and had a high level of involvement with plants also had greater involvement in water conservation, and tended to be more engaged in water conservation activities.…”
Section: Homeowner Perceptions Of Water Conservation In the Landscapementioning
confidence: 99%
See 2 more Smart Citations
“…Consumers placed a higher relative importance on plant water use in the landscape compared to use in production and preferred fresh-water to recycled water or a blend of fresh-and recycled water [24]. Furthermore, consumers who accurately perceived they were in a drought situation exhibited different attitudes and behaviors compared to individuals who did not accurately perceive they were in a drought situation [25]. Pro-water conserving attitudes and behavior are more likely observed among individuals with greater plant purchases and who place a higher value on activities in a landscaped environment [26].…”
Section: Consumer and Grower Perceptionsmentioning
confidence: 99%